The Use of Syllable Method in The Form of Picture Paper As An Innovation in The Beginning Reading Ability of Garde 1 Students of SD Plus Darul Hikmah - Sholeha, Amanda Ratu; Putri, Shinta Octaviana; Triana, Dewi; Lestari, Nurul Dwi (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This study aims to describe the application of the syllable method in the form of illustrated paper to grade 1 elemtary school students, which based on the facts in field there are still many students who are less able to spell. Therefore, the application of the syllable method in the from of illustrated paper is effectively used for students to read fluently without spelling. This research uses a descriptive qualitative method with a type of case study research that aims to explain a phenomenon by collecting data. The result of this research is that the syllable method in the from of illustrated paper can improve reading skills, especially beginning reading in students 1 SD Plus Darul Hikmah. It can be seen from the improvement of students' reading ability. Before the application of the syllable method in the form of illustrated paper there were 5 out of 22 students who were not fluent in reading and could not read. However, after using the syllable method in the form of illustrated paper, students are more interested in reading. This is also inseparable from the role of parents at home who must continue to accompany their children to learn to read. In order for this syllable method to be achieved as expected, it is better for teachers to map students' beginning reading abilities and then communicate with parents, it is hoped that what has been taught at school can be continued at home to further improve students' beginning reading learning.